Advancements in the treatment of hypothyroidism with L-T4 liquid formulation or soft gel capsule: an update. (4th May 2017) - Fallahi, Poupak; Ferrari, Silvia Martina; Ruffilli, Ilaria; Ragusa, Francesca; Biricotti, Marco; Materazzi, Gabriele; Miccoli, Paolo; Antonelli, Alessandro
ABSTRACT: Introduction: The most recent advance concerning levothyroxine (L-T4) therapy is the development of novel oral formulations: the liquid preparation, and the soft gel capsule. Areas covered: This review evaluates the most recent clinical studies about these new formulations. The liquid formulation has been shown to overcome: the food and beverages intereference with L-T4 tablets absorption, caused by food or coffee at breakfast; malabsorption induced by the increased gastric pH, resulting from atrophic gastritis, or due to proton-pump inhibitors; and malabsorption after bariatric surgery. The use of liquid L-T4 has been studied also in pregnancy, newborns and infants, suggesting a better bioequivalence than tablets. Finally, liquid L-T4 is more active than tablets in the control of thyroid-stimulating hormone (TSH) in hypothyroid patients without malabsorption, drug interference, or gastric disorders, leading to a hypothesized higher absorption of liquid L-T4 also in these patients. Few studies have evaluated soft gel L-T4 with promising results in patients with malabsorption related to coffee or gastritis. Expert opinion: Liquid L-T4 (and soft gel capsules) are more active than the tablet L-T4 in the control of TSH in hypothyroid patients with gastric disorders, malabsorption, or drug interference, but also in patients without absorption disorders.